1988
DOI: 10.1073/pnas.85.1.185
|View full text |Cite
|
Sign up to set email alerts
|

Base substitutions, frameshifts, and small deletions constitute ionizing radiation-induced point mutations in mammalian cells.

Abstract: The relative role of point mutations and large genomic rearrangements in ionizing radiation-induced mutagenesis has been an issue of long-standing interest. Recent studies using Southern blotting analysis permit the partitioning of ionizing radiation-induced mutagenesis in mammalian cells into detectable deletions and major genomic rearrangements and into point mutations. The molecular nature of these point mutations has been left unresolved; they may include base substitutions as well as small deletions, inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(64 citation statements)
references
References 35 publications
2
61
0
1
Order By: Relevance
“…Thus, in the latter case repeated DNA sequences are not required. Similar sequence-directed mechanisms of deletion formation were later seen in a small pool of both spontaneous (32) and ionizing radiation-induced mutants (28) in mammalian cells. In the present study we have confirmed the presence of these two classes of deletion mutant in mammalian cells.…”
Section: Deletions Associated With Direct and Inverted Sequence Repeatsmentioning
confidence: 66%
See 2 more Smart Citations
“…Thus, in the latter case repeated DNA sequences are not required. Similar sequence-directed mechanisms of deletion formation were later seen in a small pool of both spontaneous (32) and ionizing radiation-induced mutants (28) in mammalian cells. In the present study we have confirmed the presence of these two classes of deletion mutant in mammalian cells.…”
Section: Deletions Associated With Direct and Inverted Sequence Repeatsmentioning
confidence: 66%
“…see ref. 28), the system is rapid and simple and both base changes and the two termini of deletions of 100 bp or less can be analysed from a much larger database than would otherwise be possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For an endogenous gene this involves considerable labour of isolating, cloning and subcloning. The efficiency of the cloning procedure can be optimized by biological selection (Maniatis et al, 1982;Grosovsky et al, 1987 (Miller & Barnes, 1986). The sensitivity of this method might be further increased by including tetramethylammonium chloride in the hybridization buffers, which abolishes the preferential melting at A.T v G.C base-pairs, thus making the procedure independent of the base composition of the probe (Wood et al, 1985).…”
Section: Possible Future Directionsmentioning
confidence: 99%
“…85). Others have shown that radiation breaks DNA into fragments and causes base-change mutations (Wolff, 1971;Liber et al, 1986;Grosovsky et al, 1988).…”
Section: Introductionmentioning
confidence: 99%